Intermedial Encounters in Experimental Cinema: The Body as Performance Space - Kostopoulou, Loukia; Katsaridou, Maria (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
This article sets out to investigate intermediality in experimental cinema. It explores the intermedial crossings of dance, music, and cinema and how such crossovers recondition the medium of cinema and its impact on the spectator. According to Pethö, exploring intermediality through an affective lens means looking into the “folding together of sensory experiences of different arts” (2023). Thus, the spectator is led through an enhanced experience and is gradually affected at a sensory level. This article analyzes intermedial crossovers in a short film entitled Ghosts ((LA) HORDE, 2022). The film features instances of stillness and motion and offers a diversified experience to the spectator—one which resembles a music video or dance performance one moment and a theatrical performance the next.